Development of item banks to assess financial hardship in cancer survivors using item response theory - Jones, Salene M. W.; Yi, Jean C.; Henrikson, Nora B.; Panattoni, Laura; Shankaran, Veena (Frontiers in Cancer Control and Society, 2025)
BackgroundFinancial hardship is common after a cancer diagnosis. Current financial hardship measures have advanced the field, but assessing the dimensions of financial hardship remains challenging. We created item banks to assess four financial hardship dimensions using item response theory (IRT). IRT-based item banks can be tailored to each context and used in computerized adaptive testing (CAT) to reduce participant burden.MethodsCancer survivors (n = 459) were recruited from a survivorship program and online survey panel to complete an online or paper survey. Four item banks were developed based on previous studies, expert feedback, and patient interviews: financial coping: 41 items, financial consequences: 21 items, financial depression: 15 items, and financial worry: 21 items. We used the two-parameter logistic and graded response models for analysis.ResultsThe IRT model fit well for all four item banks: financial coping root mean square error of approximation (RMSEA) = 0.06, financial consequences RMSEA = 0.03; financial depression RMSEA = 0.05; and financial worry RMSEA = 0.03. The accuracy parameters ranged from 1.01 to 6.53, indicating good reliability for each item. The severity parameters showed each item bank assessed financial hardship across two to three standard deviations, supporting content validity. Short forms were developed for financial consequences, depression, and worry.ConclusionThe item banks can be used to create brief screening measures and, using CAT, efficiently screen for each dimension of financial hardship while minimizing burden. Future research is required to assess the clinical utility of using the item banks to screen for financial hardship.